Професійна підготовка вчителів в Україні та Республіці Кіпр у ХХІ столітті: відмінні особливості - Воєвутко, Наталя (Studies in Comparative Education, 2015)
У статті висвітлено особливості інституційного, структурно-організаційного та соціального досвіду професійної підготовки вчителів в Україні та Республіці Кіпр у компаративному аспекті. Наведено ієрархію позицій науково-педагогічних працівників у Республіці Кіпр у зіставленні з їх позиціями в українському просторі вищої освіти. Проаналізовано гендерний склад педагогічних працівників і передумови географічної мобільності та економічної міграції вчителів. В статье освещены особенности институционального, структурно-организационного и социального опыта профессиональной подготовки учителей в Украине и Республике Кипр в компаративном аспекте. Приведена иерархия позиций научно-педагогических работников в Республике Кипр в сопоставлении с их позициями в украинском пространстве высшего образования. Проанализированы гендерный состав педагогических работниковв, предпосылки географической мобильности и экономической миграции учителей. The orientation of Higher Education in the Republic of Cyprus to international standards enriches the European experience of teacher training. Therefore, studying the experience of the Republic of Cyprus for borrowing ideas and technologies in teacher training useful for national education and higher education becomes highly relevant. The research purpose is to identify the distinctive features of institutional, structural and organisational and social experience in teacher education in Ukraine and the Republic of Cyprus. The domestic educational sector features the following forms of ownership of higher educational institutions: public, communal and private. In the Republic of Cyprus, there are no communal ownership Universities. In the Republic of Cyprus, teacher education is only provided at university level. However, unlike Ukraine, Cyprus does not have special pedagogical universities. In the Republic of Cyprus, teacher training has two degrees of higher education: undergraduate (bachelor) and postgraduate (master and doctorate). In the Cypriot educational sector, a level «Specialist» is not available. In the Republic of Cyprus, in contrast to Ukraine, most teachers, especially in high school, are men. This is due to the social status of teachers and professors in Cypriot society and, consequently, of their salary. An indicator of differences such as the geographic mobility of teachers is also noteworthy. For example, in Ukraine graduates mainly work where there are learners. At the same time and conversely, economic migration (outflows to other sectors of economic activity) has recently quickened considerably. In the Cypriot educational environment, the teaching profession is prestigious and highly paid because the problem of economic migration is not unnoticed. Thus, differences of teaching experience in Ukraine and the Republic of Cyprus concern the following: ownership of higher education institutions; administration of higher education; educational and skill levels of specialist training; qualification requirements for getting a teacher post; the gender composition of the teaching staff; salary; geographic mobility.